THE INFLUENCE OF MARKET TO BOOK VALUE, ANNUAL TAX, AND RISK TOWARDS DIVIDEND POLICY IN BANKING COMPANY LISTED IN INDONESIA STOCK EEXCHANGE (IDX) PERIOD 2010-2014 - Ahmad, Gatot Nazir; Dewi, Fuchia Ananta; Mardiyati, Umi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2016)
The purpose of this study was to determine the effects Market to Book Ratio, Risk dan Annual Tax toward Dividend Policy in Bankingcompanies listed of Indonesia Stock Exchange in the periode of 2010-2014. This study use Market to Book Value, Annual Taxand Risk as independent variable. As for the dependent variable is a dummy variable with catagories of company gives dividend and companies not give dividend. The sample used in this study is 24 banking companies listed of Indonesia Stock Exchange in the periode of 2011-2014.The method in this study is analysis logistic regression. Research shows that Market to Book Value and Annual Taxhas positive but not significant to Devidend policy, whereas Risk has positive and significant effect to Dividend policy. Keywords: Banking Companies, Market to Book Value, Annual Tax, Risk, Dividend Policy